Analisis Pengaruh Literasi Keuangan, Tingkat Pendidikan Dan Gender Terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Sektor Ekonomi Kreatif Di Kabupaten Lombok Utara - Kinanti Risang Ayu; Siti Aisyah Hidayati; Alamsyah Alamsyah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the influence of Financial Literacy, Education Level, and Gender on the Performance of Micro, Small and Medium Enterprises (MSMEs) in the creative economy sector in North Lombok Regency. The population of this study used in this study is all MSME actors in the Creative Economy Sector in North Lombok Regency. The data collection method uses the survey sample method. The data collection technique uses an interview technique, which is where several questions are on the questionnaire. In addition, this study used a sample of 349 respondents with a sampling method, namely purposive sampling. This type of research is causal associative research with quantitative techniques. This research data processing uses smartPLS 3. The results of this study show that financial literacy (X1) has a significant positive effect on the performance of MSMEs (Y) in North Lombok Regency. The level of education (X2) has a significant positive effect on the performance of MSMEs (Y) in North Lombok Regency. Gender (X3) does not affect the performance of MSMEs (Y) in North Lombok Regency.